DEVELOPMENT OF A PJBL-BASED MODULE TO IMPROVE CREATIVE THINKING IN JUNIOR HIGH SCHOOL LEVEL STUDENTS: SYSTEMATIC LITERATURE REVIEW - Adibah, Bunga; Ilhami, Aldeva; Permana P, Niki Dian (PROGRES PENDIDIKAN, 2024)
This research was conducted to analyze literature related to the development of PJBL-based modules to improve creative thinking in junior high school students. The aim of this research is to select articles that are suitable for analysis related to the Development of Pjbl-Based Modules to Improve Creative Thinking in Middle School Students. The benefit of this research is to make it easier for researchers to obtain literature that is suitable for analysis related to the title of the research that will be carried out by the researcher. The method of this research is to use the PRISMA method, which is a method that has steps, namely identification, screening, eligibility, and inclusion. The conclusion of this research is that the PRISMA method is a systematic literature review type research method which aims to make it easier for researchers to carry out research whose research results are based on the results of literature analysis that has been selected in stages through several systematic procedures. Based on the results of the PRISMA method carried out by researchers, 7 pieces of literature were obtained that were suitable for analysis. As a result of the PRISMA method, which was carried out to select several literatures, the total number of literatures that were excluded or not suitable for analysis was 1,989 literatures.